Developing Student Executive Function Skills Through Teacher Learning Management - Kamphinit, Phramaha Wachiravit; Tungkunanan, Pariyaporn; Sisan, Boonchan (My University, 2023)
This research investigated teacher learning management (TLM) approaches to promote student executive function (SEF) skills in higher education teacher development in Thailand. The informants were nine academic experts with 6-42 years each of TLM and SEF skill development and teaching expertise. The contents from the interviews were analyzed to summarize the essence and used in drafting an educator TLM plan to promote student executive function thinking skills. Data analysis used content analysis techniques consisting of four steps: data reduction, data formatting, conclusions, and confirmations. Results revealed that the teacher learning management methodology used in promoting SEF thinking skills consisted of five elements. These included 1) TLM definition problems, 2) setting goals for TLM, 3) determining content for TLM, 4) TLM implementation, and 5) TLM assessment. The study contributes to the literature that SEF skill education and development and teacher learning management are critical elements in a student teacher’s development and a nation’s future economic success and sustainability.
Keywords: executive functions; student teachers; teacher learning management; Thailand; working memory